2011
DOI: 10.1242/dev.055038
|View full text |Cite
|
Sign up to set email alerts
|

The Cdc14B phosphatase contributes to ciliogenesis in zebrafish

Abstract: SUMMARYProgression through the cell cycle relies on oscillation of cyclin-dependent kinase (Cdk) activity. One mechanism for downregulating Cdk signaling is to activate opposing phosphatases. The Cdc14 family of phosphatases counteracts Cdk1 phosphorylation in diverse organisms to allow proper exit from mitosis and cytokinesis. However, the role of the vertebrate CDC14 phosphatases, CDC14A and CDC14B, in re-setting the cell for interphase remains unclear. To understand Cdc14 function in vertebrates, we cloned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 84 publications
0
24
0
Order By: Relevance
“…Among them is Cdc14b, an antagonist of Cdk1, which was found to be essential for proper ciliogenesis and ciliary length regulation in zebrafish (Clement et al, 2011). Additionally, the spindle checkpoint regulator BubR1 was found to be required for proper primary cilium formation in fish and humans (Miyamoto et al, 2011).…”
Section: Cilium Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them is Cdc14b, an antagonist of Cdk1, which was found to be essential for proper ciliogenesis and ciliary length regulation in zebrafish (Clement et al, 2011). Additionally, the spindle checkpoint regulator BubR1 was found to be required for proper primary cilium formation in fish and humans (Miyamoto et al, 2011).…”
Section: Cilium Formationmentioning
confidence: 99%
“…Modulation of several cell cycle related kinases can alter ciliary length. In zebrafish Cdc14b, the phosphatase that antagonizes Cdk1, was required for both primary and motile cilia to reach full length (Clement et al, 2011). In Chlamydomonas , a hypomorphic mutation of a CDK related kinase Lf2p results in excessively long flagella, while null mutants have stumpy flagella that are often of unequal flagellar length (Tam et al, 2007).…”
Section: Cilium Maintenancementioning
confidence: 99%
“…The cilia length phenotype was specific to hCDC14A and was not observed in cells lacking the paralogue hCDC14B. In contrast to RPE1 cells, cdc14A or cdc14B depletion in zebrafish led to shorter cilia [14,33], Presently, it is unclear why inactivation of CDC14A in zebrafish and human cells impacts cilia length in opposite ways. Variations in cilia phenotypes between organisms upon inactivation of orthologs have been reported before [34].…”
Section: Discussionmentioning
confidence: 96%
“…These similarities suggest conservation with Cdc14A, however, our observations of cdc-14 function are more consistent with the reported role of human Cdc14B in the control of G 1 progression (Rodier et al, 2008). Since Cdc14B has also been associated with DNA-damage checkpoint (Bassermann et al, 2008), meiotic progression (Schindler and Schultz, 2009), centriole replication (Wu et al, 2008) and most recently, ciliogenesis (Clement et al, 2011), it will be interesting to see if similar defects are revealed in cdc-14 mutant worms. Since C. elegans cdc-14 acts as a component of a larger regulatory network, we expect that future studies of Cdc14 in higher organisms will connect specific developmental pathways to cell-cycle regulation and provide further insights into the coordination of development and cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%